Validation of an oncoplastic breast simulator for assessment of technical skills in wide local excision. Issue 3 (17th December 2015) - Leff, D. R.; Petrou, G.; Mavroveli, S.; Bersihand, M.; Cocker, D.; Al‐Mufti, R.; Hadjiminas, D. J.; Darzi, A.; Hanna, G. B.
Abstract : Background: Simulation enables safe practice and facilitates objective assessment of technical skills. However, simulation training in breast surgery is rare and assessment remains subjective. The primary aim was to evaluate the construct validity of technical skills assessments in wide local excision (WLE). Methods: Surgeons of different grades performed a WLE of a 25‐mm palpable tumour on an in‐house synthetic breast simulator. Procedures were videotaped (blinded), reviewed retrospectively, and independently rated against a procedure‐specific global rating scale by two consultant breast surgeons. Specimen radiographs were obtained and the macroscopic distance from the 'tumour' edge to the resection margin was recorded in four cardinal directions. Expert consensus was used to construct an Oncoplastic Deviation Score (ODS), assigning points for excessively wide (more than 10 mm) and, conversely, close (less than 5 mm) macroscopic margins. Results: Thirty‐four surgeons (12 consultant surgeons, 12 specialty trainees and 10 core trainees) participated in the study. Video‐based rating scores varied hierarchically with operator expertise ( P < 0·050). Inter‐rater reliability was excellent (α ≥ 0·80, P < 0·050 for all scales), and inter‐rater agreement was moderate (κ = 0·132–0·361, P < 0·050 for all scales). Statistically significant differences were observed on pairwise comparisons between each grade of surgeon in scores for 'exposure', 'skin flap development', 'glandular remodelling', 'skin closure' and 'final product review' ( P < 0·050). Consultants received significantly fewer ODS points than specialty trainees ( P = 0·012) and core trainees ( P = 0·028). Compared with experts (median 9·0 mm), wider margins were observed amongst specialty trainees (median 12·0 mm) and narrower margins amongst core trainees (median 7·1 mm) ( P = 0·001). Conclusion: Video ratings of performance and a proposed ODS differentiate surgeons based on technical skills in WLE and may be useful for objective assessment of breast surgery trainees. Abstract : Practice safely for good cosmesis